2016
DOI: 10.3390/technologies4030028
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Assistive Technologies for Mobility and Their Implications for Active Ageing

Abstract: Purpose: Active ageing is defined as the process of optimizing opportunities for physical, social and mental health to enable older people to actively take part in society without discrimination and to enjoy independence and good quality of life. The World Health Organization assumed this to be a process for increasing and maintaining an individual's participation in activities to enhance his/her quality of life. In this survey, the authors addressed the following question: is assistive technology (AT) for mob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…According to our findings, social participation does not seem to be associated to the psychosocial impact of the PW, similar to what was demonstrated by Buning, Angelo and Schmeler, who found no significant relationship between the psychosocial impact of powered mobility devices and the users' occupational performance [16]. Contrarily, a study by Martins and collaborators demonstrated a relation between the higher psychosocial impact scores and the better performance in social participation, regarding different types of AT [10]. The fact that there was no correlation between the psychosocial impact and participation profile might mean that they had such severe physical limitations that, despite the positive psychosocial impact of the PW, it is not enough to attenuate these limitations and to improve performance in the activities of the daily living and social roles.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to our findings, social participation does not seem to be associated to the psychosocial impact of the PW, similar to what was demonstrated by Buning, Angelo and Schmeler, who found no significant relationship between the psychosocial impact of powered mobility devices and the users' occupational performance [16]. Contrarily, a study by Martins and collaborators demonstrated a relation between the higher psychosocial impact scores and the better performance in social participation, regarding different types of AT [10]. The fact that there was no correlation between the psychosocial impact and participation profile might mean that they had such severe physical limitations that, despite the positive psychosocial impact of the PW, it is not enough to attenuate these limitations and to improve performance in the activities of the daily living and social roles.…”
Section: Discussionsupporting
confidence: 90%
“…There was no evidence of negative impact of the AT due to stigmatization, as suggested in other studies [31,32], since the self-esteem level is about the same as competency and adaptability. There was no relationship between the psychosocial impact of the PW and users' age, which indicates that the AT could be beneficial at any age, making sense to be prescribed through the lifespan, also shown by Martins and collaborators [10].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…35 Each item is scored from -3 (maximum negative impact) to +3 (maximum positive impact), indicating the impact of using an assistive device. 35 Taylor et al 24 reported scores double those reported by Barrett et al 22 Differences between the device type (implantable: surface FES) and intervention time (128 days: 18 weeks) may have accounted for the enhanced results observed by Taylor et al 24 In a study investigating the effect of mobility assistive devices in older adults (>45 years), 36 the PIADS domain scores were lower than those reported by Taylor et al, 24 suggesting that FES may have equivocal effects compared to other assistive device interventions. The PIADS is responsive to variables such as device stigma and the functional features of the device.…”
Section: Discussionmentioning
confidence: 96%